A Patient‐Centered Approach to Counseling Patients With Head and Neck Cancer Undergoing Human Papillomavirus Testing: A Clinician's Guide. (23rd January 2013) - Chu, Amy; Genden, Eric; Posner, Marshall; Sikora, Andrew
Abstract : The International Agency for Research on Cancer and the National Cancer Institute have acknowledged human papillomavirus (HPV)‐16 as an independent risk factor for oropharyngeal cancer (OPC). HPV‐positive oropharyngeal cancer (HPVOPC) is a sexually transmitted entity that is on the rise; within the next 10 years, the annual number of HPV‐associated OPC cases is projected to exceed the annual number of cervical cancer cases in the United States. Recognition of HPV status in OPC has broad implications beyond the traditional oncological concerns of timely diagnosis, accurate staging, and appropriate treatment of cancer patients. The National Comprehensive Cancer Network recommends testing the tumor site for HPV‐status during OPC management; it is likely this will become a standard component of care for patients with high‐probability tumors of the oropharynx. As the practice of HPV testing becomes more common, it behooves providers to be able to adequately address the concerns of patients with HPVOPC. Although there are currently few relevant studies focusing on this population, existing literature on HPV‐infected women and patients with cervical cancer strongly supports the concept that patients with HPVOPC need education to optimally address concerns such as self‐blame, guilt, intimacy, and interpersonal relationships. When HPV testing is done, it should be accompanied by evidence‐driven and patient‐centered counseling to best minimize negative psychosocial outcomes and ensure optimum health promotion. Based on the current state of the literature, this article is intended to be a reference for physicians to effectively manage psychosocial outcomes when diagnosing patients with HPV‐associated OPC. Abstract : Human papillomavirus (HPV)‐16 is an independent risk factor for oropharyngeal cancer (OPC). This article is intended to be a reference for physicians to effectively manage psychosocial outcomes and ensure optimum health promotion when diagnosing patients with HPV‐associated OPC.